Global Trends & Challenges in Water Science, Research and Management - Li, Hong (IWA Publishing, 2016)
The global water challenge is unprecedented. Climate change, rapid urbanisation, increasing consumption and demand for food and energy, and changing land use, will leave few countries and communities unaffected. The demand for water and sanitation services is greater than it has ever been, and water has never been higher on the agenda. The Sustainable Development Goals (SDGs) not only provide a framework to address water challenges, they put water at the centre of the global agenda on sustainable development. This presents opportunities for the water sector to develop innovative solutions and scale-up best practice. Water management is a complex multi-disciplinary topic, and water professionals come in many different shapes. One of the unique strengths of IWA is bringing together experts from across the globe and specialisations into communities of practice, IWA's Specialist Groups. Connecting people from across disciplines and across national boundaries accelerates the science, innovation and practice that can make a difference in addressing water challenges and pushes the sustainability agenda. The Global Trends and Challenges in Water Science, Research and Management compendium draws upon the expertise of IWA's specialist groups who have identified the hot topics, innovations and global trends in water science, research and management that will have impact in solving global water challenges. The compendium highlights a diversity of approaches, from detailed technical and scientific aspects to more integrated approaches.